2021
DOI: 10.1007/s00345-021-03668-8
|View full text |Cite
|
Sign up to set email alerts
|

Retropulsion force in laser lithotripsy—an in vitro study comparing a Holmium device to a novel pulsed solid-state Thulium laser

Abstract: Purpose To investigate retropulsion forces generated by two laser lithotripsy devices, a standard Ho:YAG and a new pulsed solid-state Thulium laser device. Materials and methods Two different Dornier laser devices were assessed: a Medilas H Solvo 35 and a pulsed solid-state Thulium laser evaluation model (Dornier MedTech Laser GmbH, Wessling, Germany). We used a 37 °C water bath; temperature was monitored with a thermocouple/data-logger. Representative set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…This was also consistent with the preclinical study reported by Petzold et al. [38], which illustrated that compared to the Holmium:YAG laser, the TFL was able to render faster stone ablation and lower retropulsion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was also consistent with the preclinical study reported by Petzold et al. [38], which illustrated that compared to the Holmium:YAG laser, the TFL was able to render faster stone ablation and lower retropulsion.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, when treating ureteric stones using URS with better pulse control, the degree of retropulsion was significantly lesser for TFL compared to Ho:YAG without a MOSES setting. This was also consistent with the preclinical study reported by Petzold et al [38], which illustrated that compared to the Holmium:YAG laser, the TFL was able to render faster stone ablation and lower retropulsion.…”
Section: Meta-analysis Findings Compared To Preclinical Studies and P...supporting
confidence: 92%
“…The Ho:YAG laser has been the favored lithotripter for the treatment of urinary calculus since shortly after its introduction in the 1990s [1][2] because it can fragment all calculus compositions and produces less calculus migration (retropulsion) during treatment than the short-pulsed lasers [3]. Although the lamp-pumped Ho:YAG laser has been commercialized for ureteroscopic laser lithotripsy (URS) for almost 25 years, a commercially available Ho:YAG laser delivers large energy and short pulses that generate omnidirectional vapor bubbles, wasting a significant percentage of the input energy [4][5][6][7][8]. The Smart Modes of the prototype laser generate narrowly focused vapor bubbles that travel forward greater distances and deliver more energy to the target calculus.…”
Section: Introductionmentioning
confidence: 99%
“…A different laser incorporating this chemical element is Thulium: Yttrium-Aluminium-Garnet, however still being under investigation. This technology generates 120 W power, energy 0.1-3 J, and high frequency impulses up to 200 Hz, yet promises a low retropulsion effect due to long energy impulses [21,22].…”
Section: Introductionmentioning
confidence: 99%